Detailed Sunyaev-Zel'dovich study with AMI of 19 LoCuSS galazy clusters: masses and temperatures out to the virial radius - Rodriguez-Gonzalvez, C.; Shimwell, T.; Davies, M.; Feroz, F.; Franzen, Thomas; Grainge, K.; Hobson, M.; Hurley-Walker, Natasha; Lasenby, A.; Olamaie, M.; Pooley, G.; Saunders, R.; et al. (Oxford University Press, 2012)
We present detailed 16-GHz interferometric observations using the Arcminute Microkelvin Imager (AMI) of 19 clusters with LX > 7 × 1037 W (h50 = 1) selected from the Local Cluster Substructure Survey (LoCuSS; 0.142 ≤ z ≤ 0.295) and of Abell 1758b, which is in the field of view of Abell 1758a. We detect and resolve Sunyaev–Zel'dovich (SZ) signals towards 17 clusters, with peak surface brightnesses between 5σ and 23σ. We use a fast, Bayesian cluster analysis to obtain cluster parameter estimates in the presence of radio point sources, receiver noise and primordial cosmic microwave background (CMB) anisotropy. We fit isothermal β-models to our data and assume the clusters are virialized (with all the kinetic energy in gas internal energy). Our gas temperature, TAMI, is derived from AMI SZ data and not from X-ray spectroscopy. Cluster parameters internal to r500 are derived under the assumption of hydrostatic equilibrium. We find the following. (i) Different generalized Navarro–Frenk–White (gNFW) parametrizations yield significantly different parameter degeneracies. (ii) For h70 = 1, we find the classical virial radius, r200, to be typically 1.6 ± 0.1 Mpc and the total mass MT(r200) typically to be 2.0–2.5× MT(r500). (iii) Where we have found MT(r500) and MT(r200) X-ray and weak-lensing values in the literature, there is good agreement between weak-lensing and AMI estimates (with Graphic and 1.0 ± 0.1 for r500 and r200, respectively). In comparison, most Suzaku/Chandra estimates are higher than for AMI (with MT, X/MT, AMI = 1.7 ± 0.2 within r500), particularly for the stronger mergers. (iv) Comparison of TAMI to TX sheds light on high X-ray masses: even at large radius, TX can substantially exceed TAMI in mergers. The use of these higher TX values will give higher X-ray masses. We stress that large-radius TAMI and TX data are scarce and must be increased. (v) Despite the paucity of data, there is an indication of a relation between merger activity and SZ ellipticity. (vi) At small radius (but away from any cooling flow) the SZ signal (and TAMI) is less sensitive to intracluster medium disturbance than the X-ray signal (and TX) and, even at high radius, mergers affect n2-weighted X-ray data more than n-weighted SZ, implying that significant shocking or clumping or both occur in even the outer parts of mergers.